Hot dog - Coxe, Molly (New York : Random House, 2003)
A dog tries to find a way to cool off on a hot summer day on a farm.
BR
Keywords: Dogs -- Fiction; Farm life -- Fiction; Summer -- Fiction; Stories in rhyme